Correlates of Pediatric CPAP Adherence - Hawkins, Stephen M.M. (J Clin Sleep Med, 2016)
STUDY OBJECTIVES: Obstructive sleep apnea (OSA) is a common pediatric condition characterized by recurrent partial or complete cessation of airflow during sleep, typically due to inadequate upper airway patency. Continuous positive airway pressure (CPAP) is a therapeutic option that reduces morbidity. Despite efforts to promote use, CPAP adherence is poor in both pediatric and adult populations. We sought to determine whether demographics, insurance status, OSA severity, therapeutic pressure, or comorbid conditions were associated with pediatric CPAP adherence. METHODS: A retrospective review of adherence download data was performed on all pediatric patients with initiation or adjustment of CPAP treatment over a one-year period with documented in-laboratory CPAP titration. Patients were grouped as CPAP adherent or non-adherent, where adherence was defined as > 70% nightly use and average usage ≥ 4 hours per night. Differences between the groups were analyzed by χ(2) test. RESULTS: Overall, nearly half of participants were CPAP adherent (49%, 69/140). Of the demographic data collected (age, ethnicity, sex, insurance status), only female sex was associated with better adherence (60.9% vs 39.5% of males adherent; odds ratio [OR] = 2.41, 95%CI = 1.20–4.85; p = 0.01). Severity of OSA (diagnostic apnea-hypopnea index [AHI] and degree of hypoxemia), therapeutic pressure, and residual AHI did not impact CPAP adherence (p > 0.05). Patients with developmental delay (DD) were more likely to be adherent with CPAP than those without a DD diagnosis (OR = 2.55, 95%CI = 1.27–5.13; p = 0.007). Female patients with trisomy 21 tended to be more adherent, but this did not reach significance or account for the overall increased adherence associated with female sex. CONCLUSIONS: Our study demonstrates that adherence to CPAP therapy is poor but suggests that female sex and developmental delay are associated with better adherence. These findings support efforts to understand the pathophysiology of and to develop adherence-promoting and alternative interventions for pediatric OSA. CITATION: Hawkins SM, Jensen EL, Simon SL, Friedman NR. Correlates of pediatric CPAP adherence. J Clin Sleep Med 2016;12(6):879–884.